ANALISIS IMPLEMENTASI PSAP NO.07 TENTANG AKUNTANSI ASET TETAP PADA BALAI PENYANTUNAN LANJUT USIA â€œSENJA CERAHâ€ - Nikijuluw, Misye; Tinangon, Jantje; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Goverment Accounting Standards (PSAP)Â  No. 07 is the standard for accounting of fied assets in order to generate reliable information in the financial statements. The purpose of this study is to determine whether or not the implementation of PSAP No. 07 is appropriate. The center for advanced arrangement of brightness in inventory cards,transactions,and financial statements. Method used is descriptive.Results show BPLU â€œSenjah Cerahâ€ that the classification of disclosure is appropriate and disposal, fixed assets with after acquisition depreciates with PSAP No. 07 but it should be an actual fied assets value notKeywords : PSAP 07, Fixed Assets